Al-Dānī and the Codification of Qur'anic Waqf-Ibtidā' - Wahidi, Ridhoul; Putra, Afriadi; Nasrullah; Amaruddin; Karima, Nur (JOURNAL OF QUR'AN AND HADITH STUDIES, 2025)
This study explores the concept of waqf and ibtidā’ in the recitation of the Qur’an by analyzing al-Dānī’s book al-Muktafā fī al-Waqf wa al-Ibtidā’. As a crucial instrument in maintaining the semantic and theological integrity of the sacred text, this discipline integrates grammatical analysis, qur’anic exegesis, and qirā’āt. Al-Dānī classified waqf into four categories: waqf tām, kāfī, ḥasan, and qabīḥ—based on a multidisciplinary synthesis of oral transmission (riwāyah) and literary understanding (dirāyah), with reference to 20 classical authorities, 150 exegetical issues, and 617 grammatical studies. This qualitative research, grounded in content analysis, reveals al-Dānī’s influence on subsequent scientific codifications, such as the expansion of the waqf classification into eight types by Zakariyyā al-Anṣārī and the consolidation of ‘Uthmānī’s rasm criteria in Aḥmad al-Ashmūnī’s Manār al-Hudā. The findings affirm the relevance of isnād-based methodology in preserving the authenticity of the Qur’an while highlighting the dialectic between technical precision and interpretive flexibility within the Islamic scholarly tradition.